2015
DOI: 10.20868/ade.2015.3037
|View full text |Cite
|
Sign up to set email alerts
|

Reciclado de placas de yeso laminado aligeradas con residuos de poliuretano = Recycling of gypsum plasterboard lightened with polyurethane waste

Abstract: Este trabajo presenta los resultados de un proceso experimental de reutilización de residuos obtenidos de desechos de placas de yeso laminado elaboradas con residuos poliméricos de origen industrial (espuma de poliuretano) y reforzadas con fibras de polipropileno, para la fabricación de nuevas placas de yeso laminado. Para ello, se expone la metodología de reciclado de placas prefabricadas buscando de esta forma aumentar el ciclo de vida del yeso y de los residuos de poliuretano empleados. Para ello se detalla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…It is observed that water uptake reduced by 42.59-57.41-62.9 6% respectively in the 50-60-70%PW compounds compared to the reference compound, exceeding the 40% reduction in capillary water absorption achieved in other studies carried out with gypsum matrix and polyurethane polymer waste [33]. The compound with the lowest capillary water absorption capacity was E0.8-70PW (2.0 mm/min) and the one with the highest was E0.8-50PW (3.1 mm/min).…”
Section: Capillary Water Absorptionmentioning
confidence: 54%
“…It is observed that water uptake reduced by 42.59-57.41-62.9 6% respectively in the 50-60-70%PW compounds compared to the reference compound, exceeding the 40% reduction in capillary water absorption achieved in other studies carried out with gypsum matrix and polyurethane polymer waste [33]. The compound with the lowest capillary water absorption capacity was E0.8-70PW (2.0 mm/min) and the one with the highest was E0.8-50PW (3.1 mm/min).…”
Section: Capillary Water Absorptionmentioning
confidence: 54%
“…There are investigations oriented towards the design of improved gypsum mortars through the inclusion of rigid polyurethane foam waste [33][34][35][36]. Nevertheless, no references have been found to prefabricated construction materials that integrate polyurethane waste The Life Repolyuse project proposed, to good effect, the manufacture of gypsum panels with polyurethane waste, for their use in the manufacture of technical roofs [19].…”
Section: Introductionmentioning
confidence: 99%